Nanomaterials for biomolecules sensing : germanene modified screen printed electrodes for the chronoamperometric detection of histamine in fish samples - Veronica Pereira (Nanyang Technological University, 2022)
Histamine is a biogenic amine that can be found at high concentrations in rotten food such as fish and meat. High histamine consumption could lead to scombroid poisoning that has serious side effects such as hypertension, vomiting and diarrhoea. Hence, this study investigates the chronoamperometric detection of histamine using germanene modified screen printed electrodes (SPE) to allow for sensitive and portable analysis of fish samples during transportation and storage. To formulate an effective sensor, the electrochemical properties and stability of histamine were investigated to determine an optimum protocol for chronoamperometric detection. The characteristics of three germanene nanomaterials were also investigated to determine the most suitable material for the detection of histamine. Lastly, the decarboxylation interaction between histamine and diamine oxidase to form imidazole acetaldehyde was utilised as the main chemical interaction. A secondary interaction also occurs, whereby the mediator species potassium hexacyanoferrate (III) gets reduced through its interaction with the newly formed imidazole acetaldehyde. The reduction of potassium hexacyanoferrate (III) which occurs at the low potentials of +0.2 V was used to indirectly measure the histamine concentration present in the sample. Through the studies, a hydrogenated germanene modified SPE with a calibration range of 0.01-150 mgL-1 was developed and tested on real tuna samples. The sensor proved to be highly effective in measuring the concentration of histamine present in real tuna samples while also being fast, cost-efficient, and highly sensitive.